Synergistic Action of Sodium Selenite with some Antidepressants and Diazepam in Mice - Ewa Kędzierska; Lila Dąbkowska; Paweł Obierzyński; Magdalena Polakowska; Ewa Poleszak; Piotr Wlaź; Katarzyna Szewczyk; Jolanta Kotlińska (MDPI AG, 2018)
Background: The antidepressant and anxiolytic effects of selenium (Se) have been proven in many studies. This work was aimed at confirming these activities of its inorganic form—sodium selenite—and examining the possible synergy of action with antidepressants and diazepam. Methods: The antidepressant- and anxiolytic-like activity of Se was assessed using forced swim tests (FSTs) and elevated plus-maze test (EPMs). Spontaneous locomotor activity was measured using photoresistor actimeters. The experiments were conducted on male Albino Swiss mice. Results: Sodium selenite (0.5 mg/kg) reduced the immobility time in the FSTs and extended time spent in the open arms of EPMs without affecting locomotor activity The combined administration of Se at an ineffective dose (0.25 mg/kg) together with imipramine (15 mg/kg), fluoxetine (5 mg/kg), tianeptine (10 mg/kg), but not with reboxetine (2.5 mg/kg), resulted in a reduction of immobility time in FSTs, and with a threshold dose of diazepam (0.25 mg/kg) led to the prolongation of time spent in the open arms of the EPM. Moreover, the antidepressant-like effect of Se (0.5 mg/kg) was significantly reduced by pretreatment with p-chlorophenylalanine (100 mg/kg). Conclusions: The results may indicate the participation of serotonergic transmission to antidepressant action of Se and GABA-ergic transmission to its anxiolytic effects.